Treatment of trigeminal neuralgia with bupivacaine HCL using a temporary epidural catheter and pain pump: Preliminary study - GÖÇMEN, GÖKHAN; DERGİN, GÜHAN (CHURCHILL LIVINGSTONE, 2012)
Objectives: Trigeminal neuralgia (TN) is a rare form of neuropathic facial pain characterised by severe paroxysmal pain in the face. The treatment for trigeminal neuropathic pain disorder continues to be a major therapeutic challenge, as relief provided by medical therapy generally decreases over time. When medical therapy fails either due to poor or diminishing responses to drugs or to unacceptable side effects, peripheral intervention or surgical management of TN should be considered. Study design: Fourteen patients (eight men and six women) who were not responsive to further medical treatment and who were diagnosed with TN previously at other health centres were selected for treatment. For this purpose, the affected nerve was infused with 60 mL (1 mL h(-1)) of 0.5% bupivacaine HCl with a pain pump via an temporary epidural catheter. Patient's visual analogue scores (VAS) were recorded on the fifth preoperative day and on postoperative day 5, 2 weeks, 1, 3, 6 and 9 months. Results: There was a significant difference between mean preoperative and postoperative VAS value at day 5, 2 weeks, 1, 3, 6 and at the end of 9 months ((68.85 +/- 1.43) (13.57 +/- 6.68) (11.43 +/- 6.70) (14.29 +/- 6.52) (20.71 +/- 6.41) (20.71 +/- 6.41) and (21.43 +/- 6.10) respectively; *P < 0.05). Two of 14 patients did not show any pain relief. Conclusions: Continuous administration of 60 mL of 0.5% bupivacaine HCl at 1 mL h(-1) with a pain pump and epidural catheter can be used as a transition treatment for patients with side effects from high-dose antiepileptic drugs and for patients awaiting neurosurgery or individuals who refuse cranial surgery. It should not be considered as an alternative treatment of neurosurgical approaches, such as MVD, which has a definite long-lasting results. (C) 2011 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: Trigeminal neuralgia; Pain pump; Epidural catheter; MICROVASCULAR DECOMPRESSION; LOCAL-ANESTHETICS; NERVE BLOCK; MANAGEMENT; ALCOHOL; TETRACAINE; INJECTIONS